2020
DOI: 10.1021/acsaem.0c00422
|View full text |Cite
|
Sign up to set email alerts
|

Potassium Treatments for Solution-Processed Cu(In,Ga)(S,Se)2 Solar Cells

Abstract: Cu(In,Ga)(S,Se) 2 (CIGSe, CIGSSe) has emerged as an attractive thin-film solar cell absorber material owing to its high light absorption coefficient and tunable bandgap. In CIGSSe processing and fabrication, the use of alkali treatments has been implemented as sodium doping is considered a requirement for obtaining high-efficiency CIGSSe solar cell devices and has been used extensively. One of the more significant developments in recent years has been the discovery of the beneficial effects that potassium post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(48 citation statements)
references
References 56 publications
0
48
0
Order By: Relevance
“…While these two specific ink types are typically distinguished in literature (colloidal inks and true solutions), hybrid methods have been reported as well. [ 60 ] To deposit the precursor ink, several solution deposition techniques can be utilized, such as doctor blade, inkjet, [ 61 ] dip‐ and spin‐coating, [ 62,63 ] on a small scale while spray‐pyrolysis, [ 64 ] screen printing, curtain‐coating, slot‐, slit‐, and die‐ casting, [ 58,65 ] commonly finds application for larger area substrates (see Figure 1 ). Notably, the inherently colloidal‐free nature of molecular ink precursors allows for a wide choice of deposition methods minimizing potential challenges such as clogging of nozzle heads (e.g., inkjet, spray coating, etc.).…”
Section: Cu(inga)(sse)2 Photovoltaicsmentioning
confidence: 99%
“…While these two specific ink types are typically distinguished in literature (colloidal inks and true solutions), hybrid methods have been reported as well. [ 60 ] To deposit the precursor ink, several solution deposition techniques can be utilized, such as doctor blade, inkjet, [ 61 ] dip‐ and spin‐coating, [ 62,63 ] on a small scale while spray‐pyrolysis, [ 64 ] screen printing, curtain‐coating, slot‐, slit‐, and die‐ casting, [ 58,65 ] commonly finds application for larger area substrates (see Figure 1 ). Notably, the inherently colloidal‐free nature of molecular ink precursors allows for a wide choice of deposition methods minimizing potential challenges such as clogging of nozzle heads (e.g., inkjet, spray coating, etc.).…”
Section: Cu(inga)(sse)2 Photovoltaicsmentioning
confidence: 99%
“…The authors further reported thinner MoSe 2 layers with the addition of Na at the CIGSSe/Mo interface (reference device MoSe 2 thickness >1 µm) reducing interfacial resistance between the CIGSSe film and Mo substrate caused by denser absorber morphology delayed selenium diffusion. [ 209 ] However, as opposed to many previous studies for vacuum CIGSSe, [ 89,204,208,209 ] the majority carrier concentration decreased from 7.2 × 10 17 to 1.8 × 10 17 cm −3 with Na addition (photoelectrochemical measurements). Subsequently, total area (TA) efficiencies of 10.7% (with anti‐reflective coating (ARC)) were achieved for Na‐treated CIGSSe devices.…”
Section: Doping In Molecular Ink‐based Cu(inga)(sse)2 Absorbers Layersmentioning
confidence: 67%
“…[ 40,85 ] Several ink coating techniques are available, including doctor blade, spin‐coating, screen printing, curtain‐coating, and die‐casting, amongst others. [ 40,86–89 ] Broadly, the liquid‐based (or non‐vacuum) deposition processes can be performed either by immersing the substrate in a precursor solution (e.g., chemical bath deposition (CBD)), [ 90 ] electrodeposition (ED) [ 91,92 ] ) or by coating the substrate with a precursor ink (IDR). [ 40 ] For recent comprehensive reviews of the different IDRs (both molecular ink (MI) and NP based), the reader is referred to.…”
Section: Cu(inga)(sse)2 Photovoltaicsmentioning
confidence: 99%
See 2 more Smart Citations